Live Cell Imaging Demonstrates Multiple Routes Toward a STAT1 Gain-of-Function Phenotype - Giovannozzi, Simone; Lemmens, Veerle; Hendrix, Jelle; Gijsbers, Rik; Schrijvers, Rik (Frontiers in Immunology, 2020)
Signal transducer and activator of transcription 1 (STAT1) gain-of-function (GOF) mutations result in a primary immunodeficiency (PID) characterized typically by chronic mucocutaneous candidiasis (CMC), but a wider phenotypic range is reported and remains unexplained from a pathophysiological point-of-view. We hypothesized that different STAT1 GOF mutations may result in distinct molecular mechanisms, possibly explaining the variable phenotypes observed in patients. We selected STAT1 GOF mutants (R274W, R321S, T419R, and N574I) that are spread over the protein and studied their dynamic behavior. All GOF mutants showed increased STAT1 phosphorylation compared to STAT1 WT. Real-time imaging demonstrated three underlying mechanisms for STAT1 GOF: (i) R274W showed a faster nuclear accumulation, (ii) both R321S and N574I showed a reduced nuclear mobility and slower dephosphorylation, whereas (iii) T419R was near-immobile in the nucleus, potentially due to enhanced binding to chromatin. These distinct molecular mechanisms might contribute to the phenotypic heterogeneity and responsiveness to JAK inhibitors.